Power politics and sexual harassment in Downtown Cairo - Walker, Cally (AUC Knowledge Fountain, 2014)
This thesis explores how the meaning and experience of space contributes to our understanding of sexual harassment in downtown Cairo. I argue that we cannot understand relationships on the street without acknowledging the various affective discourses concerning space. Experiences of the everyday social, political and economic affect men and women differently, and constitute visible contextual and temporal sites of tension. I argue that the development-esque term of sexual harassment envelopes a wide range of practices that depend entirely on the moment and context of utterance. According to a 2013 United Nations report on Egypt, 48.9% of women believe that harassment has increased since the January 2011 uprising that called for political freedom and social justice. During 2011-2014, a number of violent political events have taken place in and around downtown Cairo that are significant for the area and for the nation at large. These events affect people’s perceptions of the area depending on the individual’s class, gender, age or political persuasion among other variables. I explore how this particular social, economic and political moment and location affect the interactions between individuals in public. This research suggests that a microanalysis of movement in the street reflects wider social anxieties about social change and politics of power both domestically and internationally. Aside from political events other (although not unrelated) social and economic shifts took place in the flux between local and global. I explore how people make room for each other on the streets amidst conflicts that the neo-liberal city presents. Understanding how people view space and interact with one another reveals negotiations and tensions that are an important conversation for understanding sexual harassment.